Deformation, Temperature and Electrical Field Simulation in Composite Materials and Their Effective Calculation Characteristics; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Lyukshin P. A.; Lyukshin B. A.; Matolygina N. Yu.; Panin S. V. Sergey Viktorovich (2015, 2015)
Title screen